The Effect of Intensive Reading Approach on Students’ Reading Comprehension - Masruroh, Lailatul (Lingual Journal of Language and Culture, 2024)
The aim of the research was to determine that students' reading comprehension of narrative texts can be increased by using an intensive reading approach. The subject of this research are students at MA Ma’arif Miftahul Ulum Melirang Bungah Gresik. The sample of this research consists of 23 tenth graders students. The researcher uses a pre-experimental research design with a quantitative method. Pre-test, treatment, and post-test are the tools used in this research to gather data. The findings demonstrated that students who were taught using an intensive reading approach were more adept at reading and comprehending the text. The result of the t-score is 17.34, the degree of significance at 0.05 and the t-table with degrees of freedom (df) of 22 were 2.074. Considering that the t-score exceeds the t-table, the alternative hypothesis in this research was allowed based on the data analysis (17.34 > 2.074). The test's accuracy was determined by the data analysis. The results showed that the students' reading comprehension had been significantly affected by learning through an intensive reading approach. As a result, students reading comprehension of narrative texts is enhanced by the intensive reading approach.